First observation of the doubly charmed baryon Ξcc + - Mattson, M.; Alkhazov, G.; Atamantchouk, A. G.; Balatz, M. Y.; Bondar, N. F.; Cooper, P. S.; Dauwe, L. J.; Davidenko, G. V.; Dersch, U.; Dolgolenko, A. G.; Dzyubenko, G. B.; Edelstein, R.; et al. (American Physical Society (APS), 2002)
The first experimental evidence for one of the six predicted baryon states which contain two valence charmed quarks-the doubly charmed baryons. As such, there were many predictions of the masses and other properties of these states. The properties of doubly charmed baryons provide a new window into the structure of baryonic matter.
Keywords: Charged tracks; Charmed quarks; Doubly charmed baryon; Hadrons; Algorithms; Cerenkov counters; Computer simulation; Copper; Diamonds; Electron energy levels; Electronic density of states; Fermi level; Nuclear reactors; Probability; Protons; Charged particles